Work Ethics and Productivity of University Workers in South West, Nigeria - Oyelade, Anthonia Ayobami (NIU Journal of Humanities, 2017)
There have been a lot of complaints by students, parents, visitors and academic staff about the productivity of universities workers is generally low with debilitating consequences on their service delivery. There is therefore the need to investigate the predictive process of   work ethics as determinant of productivity of staff of universities in South-West, Nigeria. This study adopted the descriptive survey research method. The population for the study comprised all staff of universities in South-West, Nigeria. The sample consisted of 1558 non-teaching staff (734 senior and 824 junior). This was selected through the multi-stage proportional stratified random sampling technique for the Multidimensional Work Ethic Profile (r = 0.86). Two null hypotheses were tested in the study while two research instruments were used for data collection.  Analysis of data was done using Multiple Regression Analysis. Results were tested for significance at 0.05 levels. Findings revealed that work ethics jointly and individually predicted productivity (F 3,1501=355.402; p<.05 ).  Work ethics (Beta=-0.016; t=-.573; p>.05) was not a potent predictor of organizational productivity. Work ethic (Beta=-0.271; t=10.341; p<0.05) as independent variable were however not the most potent predictors of the productivity. It was also observed that, ownership type and staff cadre had no significant moderating influence on the joint and individual contributions of work ethics to the prediction of organizational productivity of staff of the universities in South-West, Nigeria. Therefore, the conclusion was reached and it was recommended that universities should always strive to establish strong work ethics for their staff. More so, public and private universities should design and circulate code of conduct as well work ethics policy to cover senior and junior staff so as to enhance productivity among their staff. Keywords:       Work Ethics, University senior/junior staff and Productivity